A cross‐sectional study on the prevalence of metabolic syndrome in psoriasis compared to psoriatic arthritis. (28th December 2012) - Bostoen, J.; Van Praet, L.; Brochez, L.; Mielants, H.; Lambert, J.
Abstract Background Increasing epidemiological evidence suggests associations between psoriasis, psoriatic arthritis (PsA) and metabolic disease. Elucidating the complex relationship between these comorbidities may have important management implications. Objective The aim of this study was to examine the difference in prevalence of metabolic disease burden between patients with psoriasis who lack arthritic manifestations (PsO) and PsA patients. Methods We performed a cross‐sectional study in 123 patients with PsO and PsA. Metabolic syndrome was defined using the new criteria developed by the International Diabetes Foundation (IDF) in 2004. Therefore, clinical examination and standard survey were performed and fasting blood samples were collected. Results One hundred and four patients were analysed, of which 49 were PsO and 55 were PsA patients. We found that prevalence of the metabolic syndrome according to the IDF criteria was significantly higher in the PsO (44.9%) compared with the PsA group (25.5%) (P = 0.037). Looking closer at the individual components of the metabolic syndrome, this difference can mainly be attributed to the significantly higher prevalence of abdominal obesity in PsO (83.7%) vs. PsA (65.5%) (P = 0.034). For other individual components of the metabolic syndrome such as triglycerides, high‐density lipoproteins, hypertension and plasma glucose, we could not show statistically significant differences between the groups. Conclusion Metabolic syndrome is more prevalent in patients with PsO than in PsA patients, mainly determined by the higher prevalence of abdominal obesity in PsO compared with PsA group.